The roles of compliance with government procurement policy: Moderating the effects between explanatory factors and sustainable public procurement practice - Jaafar M.R.; Aziz S.A.; Ramli N.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus